A legal study on the right of litigation for immigrants in Malaysia / Nur 'Aqilah Hamzah … [et al.] - Hamzah, Nur 'Aqilah; Abu Sopian, Nurul Amalina Syafmaz; Wan Kamarul Ariffin, Wan Nursalwati; Azhar, Aqilah Hani'ah (2013)
According to the Immigration Act 1959/63, Employment Act 1955 and Passport Act 1955, right provided for the migrants worker be it legal or illegal was dispersed among these few statutes. However, there are no specific laws or statutes that govern exclusively on foreign migrants alone. One of the issues is whether they were given access to a fair and just hearing when their rights are being abused. Besides that, we investigate does a right - track litigation process provided for the foreign migrants in Malaysia. The aim of this study is to analyse the adequacy of the laws and bodies that govern the immigrants especially in terms of their rights to litigation. In addition, we also give several suggestions in order to improve the laws and bodies that govern the immigrants.